Affordability of healthy diets is associated with increased food systems performance in Nigeria: state-level analysis - Daniel A. Mekonnen; Olutayo Adeyemi; Rachel Gilbert; Dare Akerele; Thom Achterbosch; Anna Herforth (Agricultural and Food Economics, 2023)
Abstract This study examines the relationships between healthy diets’ affordability and food systems performance across Nigerian states. On a composite index (FSI) constructed from key food system components, states in the southern zones perform relatively better than those in the north, whereas a higher share of households who cannot afford a healthy diet was from northern states. Findings suggest the need for more focused attention on resilience building for improved food systems especially in northern Nigeria. Results also indicate cases where unaffordability of a healthy diet remains high in the face of comparatively lower cost and vice versa, highlighting the need for more efficient and equitable food supply systems. Findings of this study further suggest that achieving affordable healthy diets would require stepping up actions to improve, among others, access to basic services (such as good roads and electricity), increased presence of financial services (such as rural banks), greater access to information and communications services (mobile phone subscription rates and increased radio/television station coverage), facilitating more favorable and predictable business environment, and promoting women’s empowerment.